2020
DOI: 10.1158/1055-9965.epi-19-0506
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Inherited Mutations in Breast Cancer Predisposition Genes among Women in Uganda and Cameroon

Abstract: Background: Sub-Saharan Africa (SSA) has a high proportion of premenopausal hormone receptor negative breast cancer. Previous studies reported a strikingly high prevalence of germline mutations in BRCA1 and BRCA2 among Nigerian patients with breast cancer. It is unknown if this exists in other SSA countries.Methods: Breast cancer cases, unselected for age at diagnosis and family history, were recruited from tertiary hospitals in Kampala, Uganda and Yaound e, Cameroon. Controls were women without breast cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 51 publications
5
45
3
Order By: Relevance
“…It is worth emphasizing that we have performed a screening of CNVs in our cohort of HC patients, resulting in the identification of two large deletions (exons 7 to 8 and exons 7 to 11), accounting for 10.5% of the PVs. To our knowledge, only a small fraction of published studies have also performed this analysis and only seven CNVs have been identified so far: exon 1 deletion [33], exon 2 deletion [34], exon 1 to 6 deletion [35], exon 5 to 7 deletion [36], exon 8 to 11 deletion [37] and two whole-gene deletions [37,38]. While no CNVs were identified in the gnomAD SV control population dataset, analysis of BARD1 CNVs in HC cohorts is strongly recommended considering the significant contribution in our series of this kind of variant.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth emphasizing that we have performed a screening of CNVs in our cohort of HC patients, resulting in the identification of two large deletions (exons 7 to 8 and exons 7 to 11), accounting for 10.5% of the PVs. To our knowledge, only a small fraction of published studies have also performed this analysis and only seven CNVs have been identified so far: exon 1 deletion [33], exon 2 deletion [34], exon 1 to 6 deletion [35], exon 5 to 7 deletion [36], exon 8 to 11 deletion [37] and two whole-gene deletions [37,38]. While no CNVs were identified in the gnomAD SV control population dataset, analysis of BARD1 CNVs in HC cohorts is strongly recommended considering the significant contribution in our series of this kind of variant.…”
Section: Discussionmentioning
confidence: 99%
“…There, the rates of inherited breast cancer range between 14.1% in Nigeria and 15.2% in Uganda and Cameroon. Rates of inherited breast cancer in African American women range between 12.4% in those 50 years and younger and 22% in those reporting a family history of cancer 9,10,24,25. This study's findings suggest that, irrespective of island of birth, native residents of Caribbean islands have high rates of inherited breast and ovarian cancer.In Barbados, 18% of patients with breast and ovarian cancer had a germline variant with only 1 recurrent, pathogenic variant in BRCA1, which was found in 4 unrelated individuals.…”
mentioning
confidence: 69%
“…A total of 265 studies were further assessed by the full-text review, of which 145 studies not meeting the criteria (described in the Methods section and Figure S1 ) were excluded. Finally, for the analysis, we included 123 studies: 120 studies from the PubMed search and 3 hand-searched studies [ 15 , 16 , 18 , 19 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , …”
Section: Resultsmentioning
confidence: 99%
“…Only five CNVs were identified in the BARD1 gene in the selected studies. Deletion of exon 1, deletion of exon 2, and deletion of the entire gene (exons 1-11) were identified in BC patients [26,81,125], while deletion of exons 8-11 and deletion of the entire gene were identified in OC patients [34]. Of note, no large deletions were reported in the BARD1 gene in gnomAD population controls (~10,800 cases tested), and only 1 deletion (exon 4-11) was identified among noncancer FLOSSIES controls (9884 cases tested).…”
Section: Large Mutations In the Bard1 Genementioning
confidence: 99%